Behavior of FDG-avid supradiaphragmatic lymph nodes in PET/CT throughout primary therapy in advanced serous epithelial ovarian cancer: a prospective study - Laasik, Maren (Cancer Imaging, 2019)
BACKGROUND: Epithelial ovarian cancer (EOC) typically spreads intra-abdominally, but preoperative evaluation with FDG PET/CT often reveals metabolically active supradiaphragmatic lymph nodes (sdLNs). Their clinical significance and behavior during treatment has not been established. METHODS: EOC patients with PET positive sdLNs at diagnosis were prospectively followed with PET/CT after primary chemotherapy and at the first recurrence. In each patient, 2 most active LNs in 5 different supradiaphramatic regions were evaluated and the size and changes in FDG uptake (SUVmax) were recorded. The patients´ overall response to primary treatment was defined with RECIST criteria. The behavior of sdLNs during chemotherapy were compared in treatment responders and non-responders. Recurrence patterns were monitored. RESULTS: Forty-one patients with 127 PET/CT scans were systematically evaluated. In pretreatment scan, 76% (31/41) of patients had FDG-avid sdLNs in multiple anatomical sites. Only a minority (22/136) of the sdLNs were enlarged in size, but their histopathologic confirmation by biopsy was not possible. Only 6/41 patients had FDG-avid sdLNs in a single surgically approachable site. The sdLNs became inactive during primary chemotherapy more often in the RECIST responders compared to the non-responders (HR 1.46 (95%CI: 1.09–1.96), p = 0.002). The size and SUVmax values did not predict treatment outcome. In 50% of the responders the same sdLNs reactivated when recurrence occurred. Persistent post-treatment metabolic activity did not predict earlier disease relapse (p = 0.59). CONCLUSION: The behavior of metabolically active sdLNs during chemotherapy supports their metastatic nature. Due to their distribution to multiple regions, the benefit of removal of reachable sdLNS seems unlikely. TRIAL REGISTRATION: NCT, NCT01276574. Registered 1 September 2010. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s40644-019-0215-7) contains supplementary material, which is available to authorized users.